2021
DOI: 10.1186/s12889-021-10705-z
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot of narcotic drugs and psychoactive substances in Kuwait: analysis of illicit drugs use in Kuwait from 2015 to 2018

Abstract: Background The misuse of illicit substances is associated with increased morbidity and mortality; thus, substance abuse is a global health concern. The Arabian Gulf region is considered a crossing point and a consumer of illicit drugs. However, a lack of laboratory-based research has limited the scientific assessment of drug misuse in the Arabian Gulf region. Thus, an up-to-date analytical representation of the drug situation is warranted. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Thus, little is known about heroin-related deaths, and most studies in the Arabian Gulf region are outdated [ 8 , 9 ]. Al-Matrouk et al reviewed these studies and found that they were mostly survey-based and lacked laboratory-based research; thus, these studies did not actually describe the real situation of drug abuse patterns in these countries [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, little is known about heroin-related deaths, and most studies in the Arabian Gulf region are outdated [ 8 , 9 ]. Al-Matrouk et al reviewed these studies and found that they were mostly survey-based and lacked laboratory-based research; thus, these studies did not actually describe the real situation of drug abuse patterns in these countries [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The alarming escalation of methamphetamine-related deaths in Saudi Arabia, which has witnessed a staggering surge of over 500 % within a mere three-year period (2016–2018) ( Al-Asmari, 2021 ), underscores the pressing need for comprehensive research and preventive interventions. Unfortunately, data from postmortem cases are rarely reported in the MENA region ( Al-Matrouk et al, 2021 , Osman and Shawoosh, 2003 ), especially those from Saudi Arabia ( Al-Asmari et al, 2023 ). Addressing this gap is crucial.…”
mentioning
confidence: 99%
“…Despite being a major global concern, the scientific literature emerging from Saudi Arabia rarely sheds light on drug-related deaths ( United Nation Office on Drugs and Crime, 2022 ). Furthermore, epidemiological studies in the MENA region are presented infrequently, leaving us with limited insights into drug-related fatalities ( Al-Matrouk et al, 2021 , Elfawal, 1999 , Osman and Shawoosh, 2003 ). Even drug seizures at customs checkpoints do not consistently align with global trends.…”
mentioning
confidence: 99%